Anti‐CD52 blocks EAE independent of PD‐1 signals and promotes repopulation dominated by double‐negative T cells and newly generated T and B cells. Issue 9 (27th May 2020) - Haile, Yohannes; Adegoke, Adeolu; Laribi, Bahareh; Lin, Jiaxin; Anderson, Colin C.
Abstract: Lymphocyte depletion using anti‐CD52 antibody effectively reduces relapses of multiple sclerosis (MS). To begin to understand what mechanisms might control this outcome, we examined the effect of a murine‐CD52‐specific mAb on the depletion and repopulation of immune cells in mice with experimental autoimmune encephalomyelitis (EAE), a model of MS. We tested whether the tolerance‐promoting receptor programmed cell death protein‐1 (PD‐1) is required for disease remission post anti‐CD52, and found that PD‐1‐deficient mice with a more severe EAE were nevertheless effectively treated with anti‐CD52. Anti‐CD52 increased the proportions of newly generated T cells and double‐negative (DN) T cells while reducing newly generated B cells; the latter effect being associated with a higher expression of CD52 by these cells. In the longer term, anti‐CD52 caused substantial increases in the proportion of newly generated lymphocytes and DN T cells in mice with EAE. Thus, the rapid repopulation of lymphocytes from central lymphoid organs post anti‐CD52 may limit further disease. Furthermore, these data identify DN T cells, a subset with immunoregulatory potential, as a significant hyperrepopulating subset following CD52‐mediated depletion. Abstract : The proportion of newly generated lymphocytes is greatly reduced in EAE. Anti‐CD52 not only reverses this decrease but it increases the frequency of these cells and the rare subset of DN T cells. These immune repopulation changes, as well as suppression of disease, occur independent of PD‐1 coinhibitory signals.